(untitled) (Journal of the College of Education for Women, 2019)
This research aims to identify the impact of the selective model in acquiring the concepts of Kurdish grammar among female students in the eighth grade, and to achieve the goal of research, the researcher selected the experimental design with partial control and dimensional testing; the sample includes basic schools in the Chim district of Chamal/ Sulaymaniyah and randomly selected the basic school (Maha Bad) to be the field of application of the experiment and the random drawing method was chosen: two out of three sections and the number of students of the two sections is (75) students; section (C) represents the experimental group that studied the rules according to the selective model and its number is (37) students, while section (A) represents the controlling group that studied the rules using the traditional way and its number is (37) students, and the researcher conducted a parity in the variables (degrees of the previous year in the Kurdish language, intelligence, previous information. The researcher prepared a test concerning the acquisition of concepts as a tool for research applied to the research groups and the experiment continued a full semester (first semester) during which the teacher of grammar taught the two groups of research according to the teaching plans and behavioral goals developed by the researcher for each topic. At the end of the experiment, the research tool has been applied for the research groups and after analyzing the results statistically using T-Test for two independent samples.